2004
DOI: 10.1161/01.res.0000137170.41939.d9
|View full text |Cite
|
Sign up to set email alerts
|

Is the Failing Heart Energy Starved?

Abstract: Abstract-The requirement of chemical energy in the form of ATP to support systolic and diastolic work of the heart is absolute. Because of its central role in cardiac metabolism and performance, the subject of this review on energetics in the failing heart is ATP. We briefly review the basics of myocardial ATP metabolism and describe how this changes in the failing heart. We present an analysis of what is now known about the causes and consequences of these energetic changes and conclude by commenting on unsol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
286
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 553 publications
(298 citation statements)
references
References 123 publications
11
286
0
1
Order By: Relevance
“…If indeed, higher energy consumption and, thus, ATP hydrolysis occurs in failing myocardium, but with an insufficient compensatory increase of NADH production by the TCA cycle, this may explain the pronounced oxidation of the NADH-pool in failing hearts [4], which may eventually result in a mismatch between ATP supply and demand. It has been suggested that such a mismatch precedes the reduction in the total cellular levels of PCr in patients with heart failure [11,99,188].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…If indeed, higher energy consumption and, thus, ATP hydrolysis occurs in failing myocardium, but with an insufficient compensatory increase of NADH production by the TCA cycle, this may explain the pronounced oxidation of the NADH-pool in failing hearts [4], which may eventually result in a mismatch between ATP supply and demand. It has been suggested that such a mismatch precedes the reduction in the total cellular levels of PCr in patients with heart failure [11,99,188].…”
Section: Discussionmentioning
confidence: 99%
“…Besides defects in EC coupling, the failing heart is energy-starved [99,187,211]. The total cellular levels of PCr, but also NAD and adenine nucleotides, are reduced in patients with heart failure [11,99,188].…”
Section: Pathophysiological Aspects Defects In Ec Coupling In Chronicmentioning
confidence: 99%
See 2 more Smart Citations
“…Cardiac mechanical efficiency constitutes another important dimension of the heart failure pathophysiology, given that unfavorable mechanical efficiency correlates with a higher wall stress and an increased tendency to ischemia 8, 9. These factors are the leading triggers for ventricular remodeling and obviously have negative prognostic implications 10, 11.…”
Section: Introductionmentioning
confidence: 99%